The Influence Of Work Quality, Trust, And Work Discipline On The Performance Of Employees Of Pakuhaji District, Tangerang Regency - Lisna Wati Odar; Dudung Hadiwijaya; M Imam Muttaqijn (UNIVED Press, 2024)
The purpose of this research is to study how work discipline, trust factors, and work quality impact employee performance in Paku Haji District, Tangerang Regency. This research used quantitative methods and involved all employees of Paku Haji District, Tangerang Regency, with a sample of 35 people. To collect data, observation and questionnaires were used. This research uses validity, reliability, classical assumptions, coefficient of determination, and hypothesis testing with the t test and F test to analyze the data. The results show that work quality, trust, and work discipline influence employee performance both partially and simultaneously. Therefore, to improve performance, these three components must be managed well.